Paraoxonase-1 55 LL Genotype Is Associated with No ST-Elevation Myocardial Infarction and with High Levels of Myoglobin. (25th March 2012) - Marchegiani, Francesca; Spazzafumo, Liana; Cardelli, Maurizio; Provinciali, Mauro; Lescai, Francesco; Franceschi, Claudio; Antonicelli, Roberto
Abstract : It is well known that serum paraoxonase (PON1) plays an important role in the protection of LDL from oxidation. PON1 55 polymorphism is currently investigated for its possible involvement in cardiovascular diseases. The objective of our study is to verify if PON1 55 polymorphism is associated with risk of acute coronary syndrome (ACS) and with biochemical myocardial ischemia markers, such as troponin I, creatine kinase (CK)-MB, myoglobin, and C-reactive protein. We analysed PON1 55 polymorphism in a total of 440 elderly patients who underwent an ACS episode: 98 patients affected by unstable angina (UA), 207 AMI (acute myocardial infarction) patients affected by STEMI (ST elevation), and 135 AMI patients affected by NSTEMI (no ST elevation). We found that individuals carrying PON1 55 LL genotype are significantly more represented among AMI patients affected by NSTEMI; moreover, the patients carrying LL genotype showed significantly higher levels of myoglobin in comparison to LM + MM carriers patients. Our study suggests that PON1 55 polymorphism could play a role in the pathogenesis of cardiac ischemic damage. In particular, the significant association between PON1 55 LL genotype and the occurrence of a NSTEMI may contribute to improve the stratification of the cardiovascular risk within a population.